Top Ten Pearls for a Successful Subscapularis Repair - Matthew J. Orringer, M.D.; Madeleine Orringer, M.D.; Ryan D. Freshman, M.D.; Eric H. Lin, B.A.; Cailan L. Feingold, B.S.; Seth C. Gamradt, M.D.; Joseph N. Liu, M.D. (Arthroscopy Techniques)
Although less common than other rotator cuff pathologies, subscapularis tears are associated with significant functional impairment. Thoughtful patient evaluation is necessary to identify patients with this important injury. Careful radiographic examination and thorough preoperative planning facilitates successful repair of subscapularis tendon tears and associated injuries. Finally, patient adherence to postoperative rehabilitation protocols allows for ultimate restoration of function. In this Technical Note, the authors outline 10 critical points regarding the evaluation, treatment, and rehabilitation of subscapularis tears supported by recent literature and institutional experience performing subscapularis repairs.